LEARNING DESIGN IN THE KURIKULUM MERDEKA AT INDONESIAN PRIMARY SCHOOLS - efendi, didik; Musyaffa; Nurwahyuni, Asih (Waniambey: Journal of Islamic Education, 2025)
Learning design plays an important role in learning in primary schools. Learning design in primary schools is a planning process carried out by teachers to achieve learning objectives. The independent curriculum provides opportunities for schools, teachers and students to innovate and improvise in learning. The purpose of this study was to describe how teachers design learning in the independent curriculum at the primary school level. The research aims to contribute to improving the quality of learning in primary schools under the Kurikulum Merdeka. This study was conducted at MIN Kota Jayapura and SDIT Qurrta A'yun Abepura, located in Jayapura. These locations were chosen because both schools have implemented the Kurikulum Merdeka since 2022. This study used a qualitative approach with a phenomenological research design to find several things related to learning design in the Kurikulum Merdeka. The results of the study indicate that in designing learning in primary schools, several principles need to be considered, namely (1) Learning must be oriented towards students; (2) Learning must be oriented towards learning objectives; (3) Learning must be oriented towards learning experiences; (4) Learning must be oriented towards sustainability. The stages in designing learning in primary schools in the Kurikulum Merdeka include: (1) Analysing student characteristics; (2) Formulating learning objectives; (3) Determining learning models, methods and media; (4) Developing assessments.